Life cycle assessment as a guide for designing circular business models in the wood panel industry: A critical review - Araújo, Cristiane Karyn de Carvalho [UNESP]; Bigarelli Ferreira, Mariane; Salvador, Rodrigo; Araújo, Camilla Kawane Ceciliano de Carvalho [UNESP]; Camargo, Bruno Silva [UNESP]; Camargo, Sâmique Kyene de Carvalho Araújo [UNESP]; Campos, Cristiane Inácio de [UNESP]; Piekarski, Cassiano Moro (Elsevier, 2022)
The objective of the present study is to use life cycle assessment (LCA) to guide the design and implementation of circular business models (CBM) in the wood panel industry towards a cleaner production. Initially, searches in the literature were carried out to select articles on LCA of wood panels, to investigate the possible synergies between LCA and CBMs in the wood panel industry. Investigations of the production system of reconstituted wood panels, with regard to both the biological and technical cycles, allowed spotting signs of existing circularity in some parts of the manufacturing stage, such as the use of wastes for combustion and generation of energy, and the use of ash from combustion processes. In order to reduce impacts, identified via LCA, CBMs for the wood panel sector were proposed, seeking to reduce the impacts identified via LCA and fill the circular gaps left by existing practices.
Keywords: Circular bioeconomy; Circular business model; Circular economy; Life cycle assessment; Wood panel industry